Adipose Derived Stem Cells Reduce Fibrosis and Promote Nerve Regeneration in Rats. Issue 10 (10th July 2018) - Di Summa, Pietro G.; Schiraldi, Luigi; Cherubino, Mario; Oranges, Carlo M.; Kalbermatten, Daniel F.; Raffoul, Wassim; Madduri, Srinivas
ABSTRACT: Peripheral nerve regeneration is critical and challenging in the adult humans. High level of collagen infiltration (i.e., scar tissue), in the niche of injury, impedes axonal regeneration and path finding. Unfortunately, studies focusing on the modulation of scar tissue in the nerves are scarce. To address part of this problem, we have evaluated the differentiated adipose derived stem cells (dASCs) for their antifibrotic and regenerative effects in a 10 mm nerve gap model in rats. Three different animal groups (N = 5) were treated with fibrin nerve conduits (empty), or seeded with dASCs (F + dASCs) and autograft, respectively. Histological analysis of regenerated nerves, at 12 weeks postoperatively, reveled the high levels of collagen infiltration (i.e., 21.5% ± 6.1% and 24.1% ± 2.9%) in the middle and distal segment of empty conduit groups in comparison with stem cells treated (16.6% ± 2.1% and 12.1% ± 2.9%) and autograft (15.0% ± 1.7% and 12.8% ± 1.0%) animals. Thus, the dASCs treatment resulted in significant reduction of fibrotic tissue formation. Consequently, enhanced axonal regeneration and remyelination was found in the animals treated with dASCs. Interestingly, these effects of dASCs appeared to be equivalent to that of autograft treatment. Thus, the dASCs hold great potential for preventing the scar tissue formation and for promoting nerve regeneration in the adult organisms. Future experiments will focus on the validation of these findings in a critical nerve injury model. Anat Rec, 301:1714–1721, 2018. © 2018 The Authors. The Anatomical Record published by Wiley Periodicals, Inc. on behalf of American Association of Anatomists